Simplified Ab Initio Molecular Dynamics-Based Raman Spectral Simulations. Issue 11 (November 2020) - Aprà, Edoardo; Bhattarai, Ashish; Baxter, Eric; Wang, ShanYi; Johnson, Grant E.; Govind, Niranjan; El-Khoury, Patrick Z.
We describe a simplified approach to simulating Raman spectra from ab initio molecular dynamics (AIMD) calculations. The protocol relies on on-the-fly calculations of approximate molecular polarizabilities using the well-known sum over orbitals (as opposed to states) method. This approach bypasses the more accurate but computationally expensive approach to calculating molecular polarizabilities along AIMD trajectories, i.e., solving the coupled perturbed Hartree–Fock/Kohn–Sham equations. We demonstrate the advantages and limitations of our method through a few case studies targeting molecular systems of interest to surface- and/or tip-enhanced Raman spectroscopy practitioners.